KEANEKARAGAMAN KULTIVAR SEMANGKA [Citrullus lanatus (THUNB.) MATSUM. & NAKAI] DI SENTRA SEMANGKA NUSAWUNGU CILACAP - Utari Dwi Kusumastuti; Sukarsa Sukarsa; Pudji Widodo (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] is a plant of Cucurbitaceae family which is include in an annual plant. In Indonesia, watermelon has diversity in its cultivar as can be seen from the stem, leaf, flower, and fruit morphology. This research is aimed to find out the diversity and the similarity relationship of watermelon cultivar in Nusawungu, Cilacap. A survey method was used in this research by taking the samples with a random sampling technique (purposive sampling). This research parameter consisted of stem, leaf, flower, and fruit morphology of each watermelon cultivar. Data of watermelon cultivar morphology were analyzed descriptively and then analyzed based on the similarity relationship with UPGMA method (Unweighted Pair Group Method with Arithmetic Mean) using the MEGA 5.05 software. The result of this research showed that there were five watermelon cultivars namely C. lanatus ‘Farmers Giant’, C. lanatus ‘Nina’, C. lanatus ‘Black Orange’, C. lanatus ‘Torpedo’, and C. lanatus ‘Bintang’. There were two groups of watermelons based on phenetic analysis namely group I consisting of C. lanatus ‘Torpedo’, C. lanatus ‘Black Orange’, and C. lanatus ‘Nina’ cultivars, group II consisting of C. lanatus ‘Bintang’ and C. lanatus ‘Farmers Giant’. The closest similarity was between C. lanatus ‘Farmers Giant’ and C. lanatus ‘Bintang’ cultivars with the dissimilarity index of 0,516. While the most distantly related was between C. lanatus ‘Nina’ and C. lanatus ‘Farmers Giant’ cultivars with the dissimilarity index of 2,338.